Accuracy of Prehospital Identification of Stroke in a Large Stroke Belt Municipality. (2nd November 2018) - Mould-Millman, Nee-Kofi; Meese, Halea; Alattas, Ibthial; Ido, Moges; Yi, Iasson; Oyewumi, Tolulope; Colman, Michael; Frankel, Michael; Yancey, Arthur
Abstract: Objective: Strokes are a leading cause of morbidity and mortality in the United States, especially in the "stroke belt" of the southeast. Up to 65% of stroke patients access care by calling 9–1-1. The primary objective of this study is to measure the accuracy of emergency medical dispatchers (EMD) and paramedics, in the prehospital identification of stroke. Methods: The study was based at Grady Emergency Medical Services, which is Atlanta, Georgia's public emergency medical services (EMS) provider. A retrospective analysis of all medically related 9–1-1 calls to Grady EMS classified as "stroke" between January 1, 2012, and December 31, 2012 was performed. A database was created using deterministic linkage between records from Grady EMS, Grady Hospital Emergency Department (ED), and the Grady Hospital Stroke Registry. Patients excluded were less than 18 years of age, had previous or concurrent head injuries, were transferred from another inpatient facility, and/or had incomplete patient records in any one of the three databases. Descriptive analysis, linear regression, and logistic multivariable regression were performed to discover the accuracy of stroke identification and contributory prehospital factors. Results: A total of 548 patients were included: 475 were transported with EMS impression of stroke and 73 with an impression other than stroke. The median age was 59 years, 87.4% were black, and 52.6% were female. Paramedics adhered to all seven elements of the Grady EMS stroke protocol in 76.4% ( n = 363) of suspected stroke cases. Sensitivity and positive predictive value for paramedic stroke identification was 76.2% and 49.3%, respectively, and for EMD, was 48.9% and 24%, respectively. Identification of hemorrhagic strokes had a relatively lower sensitivity. Paramedics were more likely to positively identify strokes when the Cincinnati Prehospital Stroke Scale (CPSS) screen was positive, or when classified by EMD as stroke. Paramedics were less likely to identify stroke in female patients. Paramedics' diagnostic accuracy was similar regardless of their adherence to the EMS stroke care protocol. Conclusions: EMD and EMS personnel in a large city in the Southeastern United States, with high stroke prevalence, had a relatively high sensitivity in identifying acute stroke patients. Paramedic accuracy was augmented by positive CPSS screening and by EMD recognition of stroke.